Framing The Iran-Israel Conflict: A Comparative Analysis of Al-Jazeera and BBC News Coverage in April 2024 - Syahirul Alim; Yusli Effendi; Agus Wahyudi (Journal of Islamic Civilization)
The Iran-Israel conflict in April 2024 attracted extensive global media coverage, with outlets like Al-Jazeera and BBC offering contrasting narratives. This study investigates their framing strategies using Semetko and Valkenburg's typology: conflict, human interest, economic consequences, morality, and responsibility frames. Galtung's peace and war journalism models provided an analytical lens to assess how these frames align with broader editorial biases and geopolitical contexts. Analyzing 34 articles, the research reveals Al-Jazeera's predominant use of the conflict frame (80%), emphasizing Iran's retaliation and regional tensions. This aligns with Galtung’s peace journalism, diagnosing systemic issues and contextualizing the conflict. Conversely, the BBC prioritized the responsibility frame (60%), heavily condemning Iran while dramatizing Israel's defense. This approach reflects war journalism, reinforcing divisions and Western-centric geopolitical narratives. The BBC's selective inclusion of human interest elements, such as civilian casualties, dramatized the narrative to evoke sympathy for Israel. Al-Jazeera's restrained use of such frames highlighted a commitment to balanced reporting but reduced emotional resonance. Neither outlet engaged with the morality or economic consequences frames, overlooking critical ethical and financial dimensions of the conflict. These findings underscore the role of editorial alignment and framing in shaping audience perceptions and policy discourses. Al-Jazeera’s approach encouraged critical engagement, fostering a nuanced understanding, while the BBC reinforced geopolitical alliances, narrowing the scope for reconciliation.